PENGARUH LINGKUNGAN INTERNAL DAN EKSTERNAL TERHADAP MINAT BERWIRAUSAHA (STUDI KASUS MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS JAMBI) - Wati, Ayu Ulya; Dahmiri, Dahmiri; Indrawijaya, Sigit (Jurnal Dinamika Manajemen, 2018)
This study examines the internal and external environmental factors on students' interest in entrepreneurship. The research was conducted at the Faculty of Economics and Business because many young people are currently entrepreneurs. The target population of this study was 1747 students of the Faculty of Economics and Business, University of Jambi. The number of samples used was 95 students using Slovin's theory. The data collection technique used is a questionnaire. The analytical tools used in this study are instrument tests consisting of validity and reliability tests, multiple linear regression analysis, t-test, f-test, and coefficient of determination test. Overall analysis calculated using SPSS version 22. The results of this study indicate that the internal and external environmental variables each have a positive and significant effect on entrepreneurial interest. At the same time, the rest is influenced by variables that significantly impact the interest in entrepreneurship.